The Influence of Psychology of Persuasion - Cialdiani, Robert. B.; Aneet, (Gyan Management Journal, 2018)
The book reveals about how the sales professionals have influenced the mind of different  individuals to leverage them. It also teaches the methods how one can influence others for making  them to accept your decisions. Cialdiniuses well-known examples, such as the Kitty Genovese  murder, to exemplify how the theories appear in practice. With clearly expressed language and  enthralling examples throughout, itis pertinent for many various disciplines. The author drawn six  "rules of thumb" or principles of persuasion from research in the field of social psychology and  explained how they can be used to persuade and convince otI:iers. In the present article, I will briefly  discuss the most important principles which everyone should use when someone tries to influence  you.
Keywords: Cialdiniuses; rules of thumb; persuasion